Mechanical Traction Test of Pineapple Leaf Fiber-Epoxy Composite - Noeriman, Abiyoga; widayani, widayani; Adhika, Damar Rastri (Indonesian Journal of Physics, 2024)
Natural fiber-based composites are widely developed to replace materials in various industries, such as furniture and sound absorbers. One of the composite properties that is often considered for its use is mechanical property. In this study, the mechanical properties of pineapple leaf fiber-epoxy composites were studied using traction tests. The composite was made by mixing of small pieces of pineapple leaf fiber with epoxy resin, then the mixture was placed in a mold and pressed with a certain pressure at 100 °C for 2 hours. Traction tests were carried out on the pineapple leaf fiber-epoxy composites with two different epoxy concentrations (11 and 17 % wt), and different manufacturing pressure (0.22; 0.65; 1.09 MPa). The traction test results show that the maximum stress (ultimate tensile strength/UTS), elongation at break (EAB) and modulus of elasticity (E) increase with increasing epoxy content. Increasing the manufacturing pressure increases modulus of elasticity. However, the maximum UTS and EAB were shown by the composite with a manufacturing pressure of 0.65 Pa, not at the higher pressure (1.09 Pa).